Syntheses of novel topical hemostatic agents based on pectin biopolymer aiming hemorrhage control: Thromboelastographic studies and non-homogeneous swelling effect - Santisteban, Oscar A.N. [UNESP]; Sacco, Guilherme M. [UNESP]; Guarnieri, Guilherme De Paula [UNESP]; Godoy, Moacir Fernandes de; Azevedo, Eduardo Ribeiro de; Nery, José Geraldo [UNESP] (Elsevier, 2022)
Topical hemostatic agents based on pectin biopolymer were synthesized and characterized by X-ray diffraction (XRD), Scanning Electronic Microscopy (SEM), Phase Contrast Microscopy, Infrared spectroscopy (FT-IR), Differential Scanning Calorimetry (DSC) and Solid State 13C MAS NMR. The pectin biofilms were crosslinked with CaCl2 using different concentrations of Ca2+ solutions ( 4.5 ×10-2 M, 2.7 ×102 M, 4.5 ×102 M). 13C MAS NMR and FT-IR data revealed that crosslinking with Ca2+ was successfully achieved, in line with the formation of egg-box type structures. The anti-hemorragic effect caused by the interaction of the red blood cells with the pectin biofilm interface was showed in details by phase contrast microscopy. The images showed that higher Ca2+ concentration (0.45 ×102 M) positively favor the coagulation cascade by facilitating the migration and an orderly stacking of the red blood cells into the pectin biofilm scaffold. The hemostatic action of the prepared pectin biofilms were analyzed by Thromboelastography (TEG). The results indicated that the hemostatic action of the biofilms is as effective as that of the hybrid materials reported in the literature, indicating that these pectin biofilms have potential to become safe topic hemostat. It was also observed a non-homogeneous swelling effect caused by the interaction between the pectin biofilms interface and blood cells which induced a rapid bending and a bucking instability that swollen the pectin network.
Keywords: Crosslinking with calcium; Egg-box structure; Pectin; Topical hemostatic agents